Chronicle of the Discalced Carmelite Convent of St. Immaculate Conception of the Blessed Virgin Mary in Lublin – a lost order book from the 17th century - Nowicka-Struska, Anna (Melusine. Old Literature and Culture, 2023)
At the beginning of the 20th century, several monastic chronicles of the Discalced Carmelite nuns were published: Vilnius, Warsaw, Krakow, and fragments of Lvov. The preserved registers show women writing according to repetitive rules, temperamental diarists, and storytellers sharing stories and gossiping on paper. Of the preserved home chronicles kept by convents of Carmelite nuns, the fate of a few remains unknown, including the chronicles of the Lublin convent of the Immaculate Conception of the Blessed Virgin Mary. Despite the book of Lublin nuns, a chronicle of the monastery of St. Joseph has remained.